2021
DOI: 10.1093/eurheartj/ehab507
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal strain is an independent predictor of survival and response to therapy in patients with systemic AL amyloidosis

Abstract: Aims Cardiac involvement, a major determinant of prognosis in AL (light-chain immunoglobulin) amyloidosis, is characterized by an impairment of longitudinal strain (LS%). We sought to evaluate the utility of LS% in a prospectively observed series of patients. Methods and results A total of 915 serial newly diagnosed AL patients with comprehensive baseline assessments, inclusive of echocardiography, were included. A total of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Therefore, other methods for cardiac response assessment have been explored. These include echocardiographic strain measurement, 15,26,27 extracellular volume measurement using cardiac magnetic resonance, 28 and functional assessment such as the 6minute walk test, 29,30 targeted therapies as well as other large studies assessing natriuretic peptide-based cardiac response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other methods for cardiac response assessment have been explored. These include echocardiographic strain measurement, 15,26,27 extracellular volume measurement using cardiac magnetic resonance, 28 and functional assessment such as the 6minute walk test, 29,30 targeted therapies as well as other large studies assessing natriuretic peptide-based cardiac response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the diagnosis of AL CA, prognosis information is also paramount to patients as well as their clinicians. The prognostic value of PE ( 24 , 42 ), LQRSV ( 31 ), impaired strain ( 43 , 44 ) and LVMWT ( 45 ) has been previously described alone. Nonetheless, to our knowledge, the joint prognostic value has not yet been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the predictive value of several echocardiographic features, such as LVEF, average strain rate, E/e' , TAPSE, and SVi (10,11). In 2011, Bhuiyan et al (14) wanted to evaluate the end-diastolic pressure-volume relation and other pressure-volume indices in patients with TTR-CA to determine how these indices change over time and whether abnormal pressurevolume relations and indices of pump function were associated with reduced survival.…”
Section: Stroke Volumementioning
confidence: 99%
“…Indeed, the disease progression is accompanied by a progressive impairment of systolic left ventricular function and a decrease in left ventricular diastolic volume, leading to a decline in stroke volume (SV) not necessarily associated with a decreased of LVEF. Recent studies have shown the predictive value of staging system based on biomarkers and several echocardiographic measurements of central cardiac function, but only few studies focused on SV (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%